Pain catastrophising in Chinese patients with breast cancer during postoperative chemotherapy: a qualitative study - Jing Ma; Jingyi Wang; Hongying Wang; Chen Tang; Yanting Zhang; Wenjia Long; Jun Zhong (BMJ Open)
Objective To investigate the pain catastrophising in patients with breast cancer during postoperative chemotherapy.Methods Objective sampling method was used to select patients with breast cancer who underwent breast surgery and received chemotherapy in a third-class hospital of Wuhan from October to December 2022 through semi-structured interview. The interview data were sorted out and analysed by content analysis method.Results A total of 11 patients were interviewed and five categories were summarised: (1) Physical memory of pain; (2) the special meaning of time; (3) disease treatment and prognosis; (4) interpersonal communication and coping; (5) personal behaviour and growth.Conclusion Patients with breast cancer have adverse pain experience during postoperative chemotherapy. The evaluation and screening of psychological variables such as pain catastrophising should be strengthened to provide new ideas for pain management.